An update on the role of (18)F-FDG-PET/CT in major infectious and inflammatory diseases - Kung, Boom Ting (Am J Nucl Med Mol Imaging, 2019)
For decades, conventional nuclear medicine techniques have been utilized for the assessment of many infectious and inflammatory diseases. Most of these techniques have limitations such as the relatively low spatial resolution, being time consuming and low sensitivity or specificity. In recent years, FDG-PET/CT has shown promising role in the management of such diseases. An expanding set of studies illustrate the multifarious roles of FDG-PET/CT in the assessment of these conditions, both systemic diseases and more regional. Specifically, PET can provide vital information at a molecular level and consequently detect the disease activity at their earliest manifestation. With the continuing research on the diagnosis and treatment monitoring of patients with infectious and inflammatory diseases, the role of PET/CT can be further extended.